Disgorgement of Profits in Canada - Smith, Lionel; Berryman, Jeff (Disgorgement of Profits, 2015)
Canadian law sometimes allows gain-based remedies for certain wrongful acts. There is a strong suggestion that gain-based remedies are available in the common law provinces for torts and perhaps breaches of contract, but the courts have been hesitant. Common law provinces have also been willing to award gain-based remedies for breaches of confidence, in the court’s discretion. In the context of infringements of intellectual property rights, which is federal law, the legislation makes clear that gain-based remedies are available, although again this is in the discretion of the court. In both common law and Quebec civil law, in situations where one person is managing the property or affairs of another in a fiduciary capacity, improper gains must be surrendered, although it is arguable that the law ascribes rights acquired by the manager to the principal as the correct legal implementation of the parties’ relationship, rather than as a remedy for wrongdoing.